Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1155/2016/9567495
|View full text |Cite
|
Sign up to set email alerts
|

Infrarenal Aorta Thrombosis Associated with H1N1 Influenza A Virus Infection

Abstract: Influenza viruses are members of the Orthomyxoviridae family, of which influenza A, B, and C viruses constitute three separate genera. Arterial thrombosis associated with H1N1 influenza A virus infection has rarely been reported. A Turkish man aged 28 years was admitted to our emergency department with dyspnea, bilateral lower extremity insensitivity, and cold. He reported symptoms of fever, myalgia, and cough, which he had had for fifteen days before being admitted to our hospital. The patient was tested for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…In addition, there have been reports of high rates of arterio-vascular complications in influenza: the incidence ratio of an admission for acute myocardial infarction, which our patient developed, during the risk interval as compared with the control interval was 6.05 (95% confidence interval, 3.86 to 9.50) [5]. However, there have been only 2 reports of acute arterial embolism complicating influenza-associated pneumonia [1,2], and we have not experienced such cases [4]. Bunce et al reported a 50-year-old woman with acute infra-renal aortic embolism who underwent surgical de-embolization, bilateral aortoiliac stenting, and left above-knee amputation [1].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, there have been reports of high rates of arterio-vascular complications in influenza: the incidence ratio of an admission for acute myocardial infarction, which our patient developed, during the risk interval as compared with the control interval was 6.05 (95% confidence interval, 3.86 to 9.50) [5]. However, there have been only 2 reports of acute arterial embolism complicating influenza-associated pneumonia [1,2], and we have not experienced such cases [4]. Bunce et al reported a 50-year-old woman with acute infra-renal aortic embolism who underwent surgical de-embolization, bilateral aortoiliac stenting, and left above-knee amputation [1].…”
Section: Discussionmentioning
confidence: 90%
“…We recently experienced a patient with influenza-associated pneumonia complicated with deep venous thrombosis, acute pulmonary artery embolism, and acute arterial embolism that presumably originated from the left ventricle (LV). To our knowledge, there have been only two reports [1,2] of acute arterial embolism complicating influenza-associated pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Deep vein thrombosis and/or pulmonary embolism have been previously described in patients with SARS [199][200][201][202] and cases of thrombosis complicating influenza-associated pneumonia have also been reported [203][204][205]. Excessive activation of the immune system in response to pathogens can lead to pathological inflammatory consequences.…”
Section: Thromboembolism and Covid-19mentioning
confidence: 99%
“…Virus (SARS-Cov2) and cytokines → damage to endotheliocytes of blood vessels → endothelial dysfunction → formation of endothelial cells and release into the blood of a large number of procoagulants and proagregants → massive thrombosis → blockage of large vessels of the brain (development of strokes), heart (development of heart attacks), lower extremities (development of gangrene of the lower extremities) → multiple organ failure The endothelial dysfunction can be an independent cause of circulatory disorders in the organ, since it often provokes angiospasm or vascular thrombosis (108,109), which in particular, is observed in some forms of ischemia. Deep vein thrombosis and/or pulmonary embolism have previously been described in patients with ILI (110)(111)(112)(113)(114) as well as the cases of thrombosis in patients with influenza associated with pneumonia (115)(116)(117).…”
Section: Viral Disruption Of Endothelial Functionsmentioning
confidence: 97%